Adolescent Loneliness and Health in Early Adulthood1. Issue 4 (23rd August 2013) - Goosby, Bridget J.; Bellatorre, Anna; Walsemann, Katrina M.; Cheadle, Jacob E.
<x xml:space="preserve">Abstract</x> The health consequence of loneliness in the early life course is an understudied topic in the sociological literature. Using data from Waves 1–3 of the National Longitudinal Study of Adolescent Health, we examine pre‐disease pathways in the relationship between adolescent loneliness and early adult health. Our results indicate that loneliness during adolescence is associated with diagnosed depression, poorer adult self‐rated health, and metabolic risk factors related to cardiovascular disease. High depressive symptoms and parent support are important pathways through which the health consequences of loneliness are exacerbated or offset. There is also evidence that lonely youth remain at higher risk for experiencing adult depression and poor self‐rated health even in the presence of equivalent levels of parental support relative to non‐lonely adolescents. Furthermore, lonely adolescent females are more vulnerable to reporting poor adult self‐rated health and being overweight or obese in adulthood. In sum, our study demonstrates the importance of adolescent loneliness for elevating the risk of poor health outcomes in adulthood.